Mixed farming in a grazing reserve in Northern Nigeria (2000)
Nigeria's main pastoral development strategy is the settlement of pastoralists in grazing reserves. The goal of the strategy is to turn such nomadic pastoralists into mixed farmers who will take up crop farming to supplement livestock farming. Using the Bobi Grazing Reserve, Niger Stale, Nigeria as case study, the attainment of this goal is evaluated by the use of structured questionnaire, interviews, field surveys, project site visitation and personal observation. From the results, ninety-five percent (95%) of settled pastoralists willingly adopted mixed farming as an economic survival strategy. This was in response to reduced herd size on settlement, in the face of declining land available for nomadism among other reasons. Average herd size of 41.5 cattle, 14.0 gnats and 7.5 sheep was insufficient to supply household income need hence settlers took up crop farming to supplement income. Annual income from livestock farming (N62,182.00) was 78.1% of total income per settler, while crop farming supplied 21.9% (N 17.400) of the income. Farmers farmed a mean 3.97 hectares out the maximum 4.00 hectares allowed in the reserve. Ninety-five percent of settlers expressed willingness to expand farm size in response to domestic needs. Thus hitherto nomadic pastoralists became mixed farmers on settling in the reserve. Mixed farming therefore appears to be an achievable goal in Nigeria’s pastoral development strategy.